REIMAGINING DEMOCRACY: THE ROLE OF DIGITAL PLATFORMS IN MODERN POLITICAL PARTICIPATION (International Journal of Food and Nutritional Sciences, 2022)
The integration of digital platforms into political participation is reshaping democratic processes in profound ways. This study explores the transformative role of digital tools in modern democracy, highlighting both opportunities and challenges. Digital platforms, including social media, e-voting systems, and online petitions, have significantly expanded political engagement by enhancing accessibility and inclusivity. They facilitate real-time communication between citizens and politicians, foster interactive campaigns, and offer new avenues for political expression. Notable examples include the widespread use of social media in the 2014 Indian general elections and the implementation of e-voting for Overseas Indian voters in the 2020 Delhi Assembly elections.These platforms have increased voter turnout and engagement, particularly among younger and marginalized populations, by providing broader access to political information and participation opportunities. However, the digital transformation of democracy is not without its challenges. The spread of misinformation, privacy concerns, and the digital divide pose significant risks to the integrity and inclusiveness of democratic processes. Misinformation campaigns and data privacy breaches undermine informed decision-making and electoral fairness, while the digital divide exacerbates inequalities in political participation.To address these challenges, there is a pressing need for effective regulation and governance of digital platforms. Ensuring transparency, protecting user privacy, and safeguarding against digital manipulation are crucial for maintaining democratic integrity. As digital tools continue to evolve, balancing their benefits with ethical considerations and regulatory frameworks will be essential for reimagining and sustaining democratic practices in the digital age. This exploration underscores the dual nature of digital platforms as both enablers and disruptors of modern democratic participation.